Emotional and Behavioral Difficulties and Impairments in Everyday Functioning Among Children With a History of Attention-Deficit/Hyperactivity Disorder - Tara W. Strine, MPH; Catherine A. Lesesne, PhD, MPH; Catherine A. Okoro, MS; Lisa C. McGuire, PhD; Daniel P. Chapman, PhD, MSc; Lina S. Balluz, ScD; Ali H. Mokdad, PhD (Centers for Disease Control and Prevention, 2006)
Introduction Attention-deficit/hyperactivity disorder (ADHD) affects 3% to 7% of school-aged children and has been associated with a variety of comorbid mental illnesses and functional impairments, largely in clinical samples. However, little is known about the spectrum of emotional and behavioral problems and areas of impairment among children with a history of ADHD in nonclinical, nationally representative samples. Methods Data were analyzed from the 2003 National Health Interview Survey, an ongoing, computer-assisted, random-sample, personal-interview survey of the noninstitutionalized U.S. population. We examined the associations between history of parent-reported ADHD diagnosis and levels of parent-reported emotional and behavioral difficulties and related impairments among a nationally representative sample of U.S. children aged 4 to 17 years (n = 8681). The extended version of the Strengths and Difficulties Questionnaire was used to measure and score levels of difficulty and impairment. Results Approximately 5.9% of children had a history of ADHD diagnosis. Children with a history of ADHD were 6 times as likely as those without ADHD to have a high level of overall difficulties including emotional, conduct, and peer problems and were 9 times as likely to manifest a high level of impairment including interference with home life, friendships, classroom learning, and leisure activities. Conclusion This study documents the significant level of current emotional and behavioral difficulties and impairments in everyday functioning experienced by children with a history of ADHD diagnosis, suggesting that people involved with the care of children - parents, health care providers, and teachers - need to be informed about the signs, symptoms, and appropriate treatment of ADHD and other comorbid disorders.